Korelasi antara lebar mesiodistal gigi dengan kecembungan profil jaringan lunak wajah orang Bugis-Makassar - Susilowati Susilowati; Sulastry Sulastry (Journal of Dentomaxillofacial Science, 2007)
Malocclusion is very closely related to the disharmony of mesiodistaltooth-width with dental arches. It is important to know the mesiodistaltooth widths before establishing the diagnosis and planning oforthodontic treatment. The ultimate goal of orthodontic treatment isfacialesthetic, which is supported by a balanced soft tissue profile. The aim ofthis cross sectional study was to investigate the correlation betweenmesiodistal tooth widths with the convexity of soft tissue profile. Theresult of the study can be used as a reference and guidance inestablishing orthodontic diagnosis and treatment planning. The numberof sample was 50 (18 males and 32 females), aged 18-27 years old.Criteria for sample selection comprised absence of interproximalcaries/filling, no tooth deformity, aged over 17 years, never undergoorthodontic treatment, the presence of teeth from the right first molarthrough the left first molar, both upper and lower, Buginese orMakassarese people, and Class I Angle malocclusion. Tooth sizemeasurements were performed on study models by using slidingcaliper. The photo of each subject was taken cephalometrically. Theangular measurement was performed on cephalogram, using Subtelny'sanalysis. The soft tissue convexity degree was represented by N-SnPog.The data was processed using SPSS program and tested byindependent t-test and correlation. It can be concluded that the meanvalue of mesiodistal width on males was greater that those on females(p<0.05), the mean of facial convexity degree on males (159.05Â°) wassmaller than those on females (162.77Â°), which was different significantly (p<0.05), and there was a very weak correlation (r<0.25) oralmost no correlation between mesiodistal tooth-width and the degree ofsoft tissue facial profile, and it was not significant statistically (p>0.05).